Reproducibility of point‐of‐care ultrasonography for central vein diameter measurement: Separating image acquisition from interpretation. Issue 8 (8th May 2017) - Lucas, Brian P.; D'Addio, Antonietta; Clark, Jennifer; Block, Clay; Manning, Harold; Remillard, Brian; Leiter, J.C.
ABSTRACT: Purpose: Central vein point‐of‐care ultrasonography must be reproducible to detect intravascular volume changes. We sought to determine which measurement step, image acquisition or interpretation, could be more compromising for reproducibility. Methods: Three investigators each acquired inferior vena cava (IVC) and internal jugular (IJV) vein ultrasonographic sequences (US) from a convenience sample of 21 hospitalized general medicine participants and then interpreted each US three separate times. We partitioned the random errors of acquisition and interpretation, attributing wider dispersions of each to larger reductions in reproducibility. Results: We analyzed 351 interpretations of 39 IVC and 432 interpretations of 48 IJV US. Reproducibility of the maximum (standard error of measurement 3.3 mm [95% confidence interval, CI 2.7–4.2 mm]) and minimum (4.8 mm [3.9–6.3 mm]) IVC diameter measurements were worse than that of the mediolateral (2.5 mm [2.0–3.2 mm]) and anteroposterior (2.5 mm [2.0–3.1 mm]) IJV diameters. The dispersions of random measurement errors were wider among acquisitions than interpretations. Conclusions: Among our investigators, central vein diameter measurements obtained by point‐of‐care ultrasonography are not sufficiently reproducible to distinguish clinically meaningful intravascular volume changes from measurement errors. Reproducibility could be most effectively improved by reducing the random measurement errors of acquisition. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45 :488–496, 2017